Effects of cassava pulp fermentation with traditional starter media on rumen fermentation, nutrients digestibility in beef cattle - Pichad Khejornsart; Theerayut Juntanam; Wacharawit Meenongyai; Metha Wanapat (Italian Journal of Animal Science)
This study examined the effects of adding traditional starter media or look-pang for the fermentation of cassava pulp (LFC) to substitute rice bran (RB) on feed intake, nutrient digestibility, and rumen fermentation. Fresh cassava pulp was mixed with a starting medium solution and the mixture was then fermented for 14 days in a barrel and sun-dried before being combined with the total mixed ration (TMR) diet. A 4 × 4 Latin square design was used to analyse the experiment, and four yearling crossbred beef cattle were allocated to receive four levels of TMR diets with LFC (0, 35, 65, and 100%). The results indicated that increasing substitution levels of LFC had a tendency to increase the total dry matter (DM) intake (p = 0.060). The digestion of DM and OM significantly improved (p < 0.05) when RB was substituted with LFC, however the digestibility of CP, NDF, and ADF was unaffected (p > 0.05). Ruminal pH remained stable (p > 0.05), while the concentration of NH3-N and total VFA increased when 65% and 100% of LFC were supplemented (p < 0.05). On the other hand, when LFC substituted for RB, the acetate-to-propionate ratio decreased linearly (p < 0.05). Increasing the level of LFC in the TMR diet significantly increased the number of bacteria and protozoa (p < 0.05). Nitrogen utilisation (NUE) increased and microbial protein synthesis improved when TMR was combined with LFC (p < 0.05). Supplementing 100% LFC enhanced nutrient digestibility and rumen ecology with increasing the microbial protein synthesis and NUE of crossbred beef cattle.